Analytical prediction of load deflection curves of external steel fibers R/C beam–column joints under monotonic loading. (15th January 2015) - Campione, G.
Highlights: Macro model for flexural behavior of external beam–column joints. Model specific for hooked steel fiber-reinforced concrete (FRC). Shear-to-moment interaction for beams and columns. Model useful for the design of ductile sub assemblages. Abstract: In this paper a simplified analytical model able to reproduce the flexural behavior of external beam–column joints under monotonic loading is presented, to be used for pushover analysis. The subassemblage (beam, column and joint) is subjected to a constant vertical load acting on the column and to a monotonically increasing lateral force applied at the tip of the beam. The model is specific for hooked steel fiber-reinforced concrete (FRC) and is designed to calculate the flexural response in the form of a load–deflection curve, of beam–column subassemblages. No bond failure and shear deformations are considered in the present paper. The model includes shear-to-moment interaction for beams and columns and is based on the determination of elastic–plastic behavior of the beam and of the columns, the latter being obtained from knowledge of the ultimate moment associated with the design axial force and deduced through a simplified moment axial force domain. The experimental results available in the literature are compared with the results obtained using the proposed model, showing good agreement. Finally, the model can be usefully utilized for the design of external joints with weak beams and strong columns.